Global Justice and the New Regulatory Regime - Gray, Kevin; Kalyalya, Kafumu (Les ateliers de l'éthique / The Ethics Forum, 2015)
In this paper we challenge the role of consent in the global order by discussing current modes of international law making in the global order. We contend that the features of state consent in international law depart substantially from those assumed by theorists of the liberal order, who subscribe, in most cases, to the realist conception of state action. We argue, against those theorists, that state consents to coercive measures, and the state’s role in carrying them out, has ceased to be central to an account of global law. We conclude that international law—often thought of as law beyond the state—now has expanded its scope to reach individuals and corporations, and that this change has important ramifications for theories of global justice.